you get he common ratio by dividing a term by the previous term
so,
15/-5 = -3
common ratio = -3
Geometric seuqence has a general term of:
![a_n=ar^(n-1)](https://img.qammunity.org/2023/formulas/mathematics/college/ap7tka3z5szz7gan7yzwlm8df4q559etdo.png)
Wher
r is common ratio
a is first term
Given,
a = -5
r = -3
We have:
![\begin{gathered} a_n=ar^(n-1) \\ a_n=-5(-3)^(n-1) \\ a_n=-5*-3^n*-3^(-1) \\ a_n=-5\cdot-3^n*-(1)/(3) \\ a_n=-(5)/(3)(3)^n \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7yhkdpjoe7lrxue3l9lvpop2iuukpkecn0.png)
12th term is basically n = 12
So, we have:
![\begin{gathered} a_n=-(5)/(3)(3)^n \\ a_(12)=-(5)/(3)(3)^(12) \\ a_(12)=-885735_{} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/njvhrtosh2y2zq79692xl3754fgi3i8upt.png)